Relational Job Design and the Motivation to Make a Prosocial Difference - Grant, Adam M. (Academy of Management Review, 2007)
This article illustrates how work contexts motivate employees to care about making a positive difference in other people's lives. I introduce a model of relational job design to describe how jobs spark the motivation to make a prosocial difference, and how this motivation affects employees' actions and identities. Whereas existing research focuses on individual differences and the task structures of jobs, I illuminate how the relational architecture of jobs shapes the motivation to make a prosocial difference.